Supplementation with Calliandra calothyrsus improves nitrogen retention in cattle fed low-protein diets - Korir, Daniel; Goopy, John P.; Gachuiri, C.; Butterbach-Bahl, Klaus; Eckard, Richard; Anderson, C. (Commonwealth Scientific and Industrial Research Organisation, 2016)
Ruminant productivity in the tropical Africa has remained low despite decades of research on animal nutrition and introduction of new breeds of animals mainly because of low-quality feeds available, especially during the dry season that is inefficiently utilised. This results in prolonged time for animals to mature and increased nutrient excretion to the environment. We conducted a study using yearling steers (n = 12, liveweight (LW) = 161.8 ± 10.89 kg) in a 3 × 3 Latin square to evaluate the effect of protein supplementation and supplementation frequency on intake, digestibility, nitrogen (N) retention and microbial N supply in cattle consuming low-protein diets. The steers were maintained on ad libitumwheat straw (DM = 877 ± 5 g/kg, crude protein (CP) = 20.0 ± 1.1 g/kg), with supplemental protein supplied as air-driedCalliandra calothyrsus leaves (DM = 897 ± 3 g/kg, CP = 257.5 ± 4.1 g/kg on a DM basis). Samples of basal diet, supplement, refusals, faecal matter and urine were collected and analysed per treatment. Supplementation increased intakes by the steers (P < 0.001), with no difference between the two supplementation frequencies (P > 0.404). Steers lost bodyweight (P < 0.05) on all treatments, but less so when supplemented. Nitrogen losses was reduced (P < 0.001) with supplementation (–33.3% vs 15.7%, s.e.m. 0.06). The increased N balance in animals receiving supplemented diets indicated that N retention actually improves with increased protein supplementation in animals fed low-protein diets, implying that improving protein supply to animals fed submaintenance diets will not only ameliorate production losses, but will actually decrease non-enteric greenhouse gas production and environmental N losses per animal product unit obtained.